RARE-15. THE MOLECULAR PROFILE OF SECONDARY MENINGIOMAS IN SURVIVORS OF CHILDHOOD NON-CENTRAL NERVOUS SYSTEM CANCERS. (1st June 2021) - Corriveau-Bourque, Catherine; Wong, Derek; van Landeghem, Frank; Snuderl, Matija; Spavor, Maria; Yip, Stephen; Eisenstat, David
Abstract: Introduction: Cranial irradiation remains part of childhood cancer therapy and secondary meningiomas are a late effect. Secondary meningiomas are reported in patients who received low and high dose cranial irradiation and arise ~ 20 years post exposure. The molecular and genetic profile of primary meningiomas has been well studied; however, only a few studies describe these in radiation-induced meningiomas (RIM). Methods: We identified patients followed at the Childhood Cancer Survivor Clinic, Stollery Children's Hospital who had a history of non-central nervous system malignancies and received cranial irradiation who developed meningiomas between clinic inception in 1971 and June 2013. Whole exome sequencing (WES) as well as DNA methylation profiling were performed for patients where tumor and germline DNA were available. Results: Of 96 patients who received cranial irradiation, 16 (16.7%) developed symptomatic meningiomas. This patient cohort is unique; all 16 patients received 2000–2400 cGy, suggesting a threshold dose. 9/16 (56%) had WHO Grade 2 meningiomas or greater and 7/16 (44%) were infiltrative. Post-surgical recurrences occurred in 43%. Patients experienced considerable morbidities directly attributable to the meningiomas or their treatment. 14 patients had samples suitable for further analysis. Preliminary results revealed that NF2 mutations were the most common (5). Other meningioma related genes with mutations identified in our patient cohort include TRAF7, AKT3, MSH4 (2), KMT2C (2), TET1 (2), KDM6A, and MLH3. Copy number alternations were noted with increased frequency on chromosomes 1p, 22q, 19q. 850k methylation analysis did not conclusively show any clustering. Ongoing studies include assessment of tumor mutation burden, RNAseq, and the mutational profile. Conclusions: This study examined RIM in patients who received similar doses of radiation for their childhood cancer. To date, our findings are consistent with previously described primary and RIM mutations. Enhanced knowledge in secondary meningiomas is crucial for accurate patient counseling, prognostication, and treatment.